Analytical Substantiation of an Antidiabetic Ayurvedic Formulation Eladi Churna through Fourier Transmission Infrared - Reddy, K. R. C. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: This study aims to evaluate possible functional group and phytoconstituents present in all the ingredients of Eladi Churna as well as in final dosage form (Eladi Churna). Materials and Methods: For infrared (IR) spectroscopy, all the samples were mixed with KBr in moisture free environment in a ratio of 1:100, then, pellets were prepared and processed for scanning. Results and Discussions: Different absorbance peaks in Fourier transmission IR (FTIR) spectrum indicates the presence of phytoconstituents such as phenols, polyphenols, tannins, carbohydrates, and glycosides. Conclusion: By the usage of FTIR different bonding interactions and presence of phytoconstituents has been evaluated in separate ingredients as well as in final formulation. FTIR, if used in a proper manner, can act as a boon in the analytical validation of herbal medicines which are a complex mixture of phytoconstituents.